Victorine Florarium: Flower Motifs in the Adam of Saint Victor’s Sequences - Libowski, Łukasz (Roczniki Kulturoznawcze, 2023)
In this article I deal with the floral imagery encountered by the reader of the sequences of Adam of Saint Victor († 1150). This author is one of the most important representatives of the school that operated for several centuries, beginning in the 12th century, at the Parisian canonical abbey of Saint Victor. There is little literature about his work in the Polish writing at the present time. The study is divided into two parts. The first is a review of the source material. Here I present successive fragments of Adam’s sequences in which floral motifs appear. When it comes to the second part of the text, I share in it some observations of a different nature, collecting them into four points. These observations are, of course, related to the relevant imagery.